Eating behaviour: How health concern, self-control and gender influence healthy food choice - Theresia Cristina Sinaga; Anna Undarwati (AcTion: Aceh Nutrition Journal, 2024)
Most Indonesians are unable to control their food choice. This factor is due to individual indifference to maintaining health, self-control, and gender. This study aimed to examine the personal factors that can influence healthy food choices. The research method used a quasi-experimental with post-test-only control group design; the total sample included 143 participants aged between 17-25 years. This study was conducted at the Psychology Laboratory of Semarang State University in September 2023. Health concerns and self-control were measured by filling out a questionnaire, and an experimental test was conducted to choose healthy food using the Fake Food Buffet. Data analysis was performed using GLM univariate test. The results of this study indicate that there is a significant influence of health concern and self-control on healthy food choices, but the results of gender analysis on healthy food choices are not significant. This means that individuals who care about health and have strong self-control choose healthy food. However, there were no differences in food choice behaviors between women and men. It can be concluded that personal factors, such as health concerns and self-control, significantly influence the choice of healthy food. This could reduce the level of obesity that will occur in the future.